Diseño de una guía metodológica para el monitoreo y control del portafolio de la dirección de apropiación de TIC, del Ministerio de tecnologías de la información y las comunicaciones. (2018)
The degree work arises from the need to contribute on the public resources investment effectiveness with the purpose of achieving the Plan Nacional de Desarrollo goals and existing sector policies, along with the available financing of each fiscal validity, to which the existence of management tools is precise to help achieve this goal. The investigation is done with a qualitative and descriptive focus, preceded with the literature revision, interviews and expert judgement. Results from the literature revision are combined with the derived information from the interviews in order to characterize the portfolio, determine the indicator matrix and the DATIC existing organizational actives. Various organizations dedicated to promote project management good practices are revised and the ones that have the portfolio standard are studied between the project management practices. Selection criteria is fixed and the two that permit a comparison are chosen. Once compared, the portfolio standard is chosen from the Project Management Institute by being the one that best applies to DATIC, taking advantage of the organizational actives that are founded Being DATIC a MinTIC area and by consequence from the public sector, the public investment context in Colombia is analyzed, as well as the planning framework with which the DATIC portfolio life cycle is immersed on the Presupuesto General de la Nación planning cycle, and to which extent it is dependent from the TIC sector policies and the Plan Nacional de Desarrollo. The process maps for the phases of the initiation, planning, execution and portfolio optimization are designed, in which the critical monitoring and control points are fixed in order to improve the portfolio management process. Additionally, a description of the activities that are realized in each process its made, as well as a table with the entries, tools, techniques and exits is made. The union of all the elements gives origin to the design of the methodological guide to the monitoring and control of the portfolio of the “Dirección de la Apropiación de TIC del Ministerio de Tecnologías de la Información y las Comunicaciones”, that constitutes the product of the degree work project. The validation process from the guide with the advisory team, DATIC component leaders and a TIC expert is done. With positive perception all the made recommendations are welcomed and all the recommended adjustments are made and finally, the expert validates the document. From the realized work, it is concluded that only a few portfolio monitoring and control studies in the public sector exist; that the portfolio benefits are perceived when the ex - post evaluation is made, which is a good practice that is eventually realized and not with the periodicity that is required to evidence the results from the portfolio management; that a future job to promote the culture of the management of public portfolios needs to be done; moreover, that the DATIC portfolio is prioritized according to the public policies, the government policies and the policies that are fixed on the Plan Nacional de Desarrollo.